Epigenetic modification of the oxytocin gene is associated with gray matter volume and trait empathy in mothers. (January 2021) - Hiraoka, Daiki; Nishitani, Shota; Shimada, Koji; Kasaba, Ryoko; Fujisawa, Takashi X.; Tomoda, Akemi
Highlights: Oxytocin gene ( OXT ) DNA methylation predicts maternal empathy (Personal Distress). OXT methylation is inversely correlated with the GMV of the right ITG. The indirect effect of ITG gray matter volumes was not significant. Abstract: Mother's empathy is an important ability for parenting behavior. Many studies have confirmed that oxytocin affects empathy, but the epigenetic background of oxytocin in maternal empathy has not yet been examined. This study examined the relationship between the oxytocin gene methylation and empathy in mothers of children in early childhood. Additionally, in order to understand a comprehensive mechanism, we also investigated changes in gray matter volume as a function of oxytocin gene methylation and empathy. The Interpersonal Reactivity Index was used to assess cognitive and affective dimensions of empathy of the 57 mothers who participated in this study. Genetic data were collected via saliva samples and analyzed to quantify DNA methylation of oxytocin gene. Gray matter volumes were investigated by means of voxel-based morphometry across the whole brain. A positive correlation was found between oxytocin gene methylation and Personal Distress, an aspect of affective empathy. Moreover, we found an inverse correlation between oxytocin gene methylation and the volume of the right inferior temporal gyrus. In a relationship with oxytocin gene methylation and empathy, the indirect effect of the inferior temporal gyrus gray matter volumes was not significant. Our findings provide empirical evidence for an epigenetic mechanism linking the oxytocin gene, structural variation of brain, and empathy in mothers. Taken together, the current imaging epigenetic findings shed new light on the understanding of the epigenetic basis of oxytocin and parental empathy.